INTERGENERATIONAL PROGRAM AND CARE: ANALYSIS OF MALAYSIA INTERGENERATIONAL MODULES, POLICIES AND GUIDELINES - Intan Liana Samsudin; Syed Iskandar Ariffin; Maimunah Sapri, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Globally, there is growing interest in strengthening intergenerational connectivity through intergenerational practices. Intergenerational practice is one of the solutions to support the social and emotional needs of a senior citizen. The rationale of intergenerational learning is essential to provide benefits for the young and the older generations while offering mutual benefits through activity. Although the intergenerational exchange exists in Malaysia, there is still a lack of evidence on the program and care modules. The research aims to analyse the evidence of modules, policies, and guidelines related to Malaysia's intergenerational program. The research objectives are to identify intergenerational historical development and modules, review intergenerational policies and care facilities' guidelines. The focus policies and guidelines review are related to social, senior citizen, and childcare scope through the content analysis method. The result shows that the community-based intergenerational module is the preference for intergenerational development in Malaysia. The intergenerational aged care module typology can be further enhanced and extended to childcare facility building as one of the alternatives to the existing intergenerational care module.